Conservation of fish diversity in protected sites and adjacent fishing areas of the Southern Mexican Pacific Ocean - Georgina Ramírez-Ortiz; Omar Valencia-Méndez; Luis Hernandez; Tania González-Mendoza; Andrés López-Pérez (PLoS ONE, 2025)
The global decline in marine biodiversity is accelerating, prompting Mexico’s government to establish marine protected areas to regulate human activities. The objective of this study was to test whether there were differences in fish taxonomic and functional diversity among protected reef sites within Parque Nacional Huatulco and adjacent non-protected (NP) zones, as well as whether the temporal trends in fish diversity, density, and biomass of commercial and non-commercial species differed in relation to these human use levels. It was hypothesized that fish functional diversity would be similar among protected and NP sites, given that fishing and tourism activities persist at protected sites. Concurrently, taxonomic and functional diversity decline was predicted, associated with decreasing commercial species due to increasing human activities in both zones. We collected data from underwater monitoring conducted by SCUBA divers (2006–2020) at 20 coral and rocky reef sites to calculate taxonomic and functional diversity metrics based on six biological traits. Functional diversity metrics were employed to analyze the resemblance among human use levels. Additionally, ecological indicators were incorporated as response variables in linear models to assess temporal changes. The results demonstrated functional diversity resemblance among human use levels, as well as temporal stability in Simpson’s dominance index and significant increases in fish species richness and density at both zones. For protected sites, significant changes in fish functional diversity (increase in functional richness and decrease in divergence and originality), could indicate positive effects of protection, such as functional redundancy increases and the capacity to maintain reef functions over time. Commercial and non-commercial species exhibited stability or increase in density and biomass at both protected and NP sites.